2009
DOI: 10.1161/circulationaha.109.870709
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted High-Density Lipoprotein Attenuates Platelet Function in Individuals With Type 2 Diabetes Mellitus by Promoting Cholesterol Efflux

Abstract: Background-Individuals with diabetes mellitus have an increased risk of cardiovascular disease and exhibit platelet hyperreactivity, increasing their resistance to antithrombotic therapies such as aspirin and clopidogrel. Reconstituted high-density lipoprotein (rHDL) has short-term beneficial effects on atherosclerotic plaques, but whether it can effectively reduce the reactivity of diabetic platelets is not known. Methods and Results-Individuals with type 2 diabetes mellitus were infused with placebo or rHDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 48 publications
(37 reference statements)
3
131
1
6
Order By: Relevance
“…Study results established that a 40 % increase in HDL cholesterol levels in patients with type 2 diabetes mellitus was associated with a 50-75 % reduction in platelet aggregation (Calkin et al 2009). A similar decrease in the aggregation of platelets was observed when isolated human platelets were incubated with rHDLs or native HDLs in vitro (Calkin et al 2009;Nofer et al 1998;Badrnya et al 2013). Native HDLs and rHDLs not only modulate platelet aggregation but also prevent platelet degranulation and spreading as well as adhesion of platelets to fibrinogen (Calkin et al 2009;Nofer et al 1998;Badrnya et al 2013).…”
Section: Hdls and Plateletsmentioning
confidence: 70%
See 2 more Smart Citations
“…Study results established that a 40 % increase in HDL cholesterol levels in patients with type 2 diabetes mellitus was associated with a 50-75 % reduction in platelet aggregation (Calkin et al 2009). A similar decrease in the aggregation of platelets was observed when isolated human platelets were incubated with rHDLs or native HDLs in vitro (Calkin et al 2009;Nofer et al 1998;Badrnya et al 2013). Native HDLs and rHDLs not only modulate platelet aggregation but also prevent platelet degranulation and spreading as well as adhesion of platelets to fibrinogen (Calkin et al 2009;Nofer et al 1998;Badrnya et al 2013).…”
Section: Hdls and Plateletsmentioning
confidence: 70%
“…First, it has been reported that HDLs can block the activation and aggregation of platelets. In a small clinical trail, 13 patients with type 2 diabetes mellitus were randomized to a single infusion of rHDLs (CSL-111) or placebo (Calkin et al 2009). Study results established that a 40 % increase in HDL cholesterol levels in patients with type 2 diabetes mellitus was associated with a 50-75 % reduction in platelet aggregation (Calkin et al 2009).…”
Section: Hdls and Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that HDL function is critically determined by the components in HDLs such as apoA‐I (apolipoprotein A‐I) 18, 19, 20. Pathological alteration of HDL metabolism imbalances HDL components and thus abrogates the protective effects of HDLs in cardiovascular events 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy volunteers receiving low doses of LPS, injection of rHDLs reduced collagen-induced platelet aggregation and modified the procoagulant state associated with endotoxemia (Pajkrt et al 1997). More recently, reconstituted HDL infusion in patients with type 2 diabetes induced a 50-75 % attenuation of platelet aggregation in response to ADP and collagen (Calkin et al 2009). In vitro, this effect was shown to be dose-dependent and remained after removal of rHDLs.…”
Section: Antithrombotic Actionsmentioning
confidence: 99%